Targeting both tumour-associated CXCR2+ neutrophils and CCR2+ macrophages disrupts myeloid recruitment and improves chemotherapeutic responses in pancreatic ductal adenocarcinoma. Issue 6 (1st December 2017) - Nywening, Timothy M; Belt, Brian A; Cullinan, Darren R; Panni, Roheena Z; Han, Booyeon J; Sanford, Dominic E; Jacobs, Ryan C; Ye, Jian; Patel, Ankit A; Gillanders, William E; Fields, Ryan C; DeNardo, David G; et al.
Abstract : Objective: Chemokine pathways are co-opted by pancreatic adenocarcinoma (PDAC) to facilitate myeloid cell recruitment from the bone marrow to establish an immunosuppressive tumour microenvironment (TME). Targeting tumour-associated CXCR2 + neutrophils (TAN) or tumour-associated CCR2 + macrophages (TAM) alone improves antitumour immunity in preclinical models. However, a compensatory influx of an alternative myeloid subset may result in a persistent immunosuppressive TME and promote therapeutic resistance. Here, we show CCR2 and CXCR2 combined blockade reduces total tumour-infiltrating myeloids, promoting a more robust antitumour immune response in PDAC compared with either strategy alone. Methods: Blood, bone marrow and tumours were analysed from PDAC patients and controls. Treatment response and correlative studies were performed in mice with established orthotopic PDAC tumours treated with a small molecule CCR2 inhibitor (CCR2i) and CXCR2 inhibitor (CXCR2i), alone and in combination with chemotherapy. Results: A systemic increase in CXCR2 + TAN correlates with poor prognosis in PDAC, and patients receiving CCR2i showed increased tumour-infiltrating CXCR2 + TAN following treatment. In an orthotopic PDAC model, CXCR2 blockade prevented neutrophil mobilisation from the circulation and augmented chemotherapeutic efficacy. However, depletion of either CXCR2 + TAN or CCR2 + TAM resulted in a compensatory response of the alternative myeloid subset, recapitulating human disease. This was overcome by combined CCR2i and CXCR2i, which augmented antitumour immunity and improved response to FOLFIRINOX chemotherapy. Conclusion: Dual targeting of CCR2 + TAM and CXCR2 + TAN improves antitumour immunity and chemotherapeutic response in PDAC compared with either strategy alone.